Transforming TVET for a Green and Digital Future: Integrating Vocational Education with Media Literacy in India" - Dr C P Rashmi; Kumar, Dr. R. Ravi (Journal of Advanced Research in Journalism & Mass Communication, 2026)
India is at a stage today where the future of education needs to be envisioned outside classrooms and textbooks. As we develop towards a greener and a digital economy, our vocational education systems, particularly TVET, have to adapt to the demands of this new world. It is no longer merely about training for trades or technical skills. The future requires that we also get students ready to think critically, communicate effectively, and navigate the complicated world of media and digital spaces. This paper discusses how India can redesign its Technical and Vocational Education and Training (TVET) by incorporating media literacy into its current structure. Taking cues from flagship national programmes such as the Skill India Mission, NEP 2020, and initiatives by the Green Jobs Skill Council, the report points out how certain states are already leading the way. Kerala’s training of solar technicians incorporates social media engagement; Tamil Nadu’s polytechnics are piloting digital storytelling; Maharashtra’s ITIs are adding communication modules beyond basic workplace competencies. These examples show that the change has begun, but there’s still a long way to go. Based on field interviews, institutional case studies, and recent academic findings, the paper argues that media literacy, when introduced thoughtfully into vocational education, can build not just employable youth, but also empowered citizens. In a world flooded with misinformation, digital tools, and online workplaces, this integration is no longer optional. This research seeks to spur discussion on why India’s vocational education has to adopt a wider skill set, one encompassing sustainability, digital literacy, and media literacy. It ends with calls for reconsidering the curriculum, spending on teacher training, and creating closer connections between industries, educators, and students. The intent is clear: to equip a workforce that’s not merely job-ready but future-ready. Underpinning these efforts are national programs like the Skill India Mission, National Education Policy 2020, and the Green Jobs Skill Council, which the research consults to explore how vocational schools, namely, Industrial Training Institutes (ITIs) and polytechnics, are starting to integrate both media education and sustainability into the curriculum. Based on case studies in Kerala, Tamil Nadu, and Maharashtra, the paper brings into focus initiatives like the integration of digital storytelling modules in media-oriented vocational courses, social media-based green practice awareness campaigns, and communication skills integrated into technical learning through training programs. The study also touches on the increasing demand for media and digital literacy in vocational trades, particularly as work roles increasingly require skills to read and create content, manage online platforms, and critically analyze digital information. Discussions with trainers, learners, and policy experts show that incorporating media literacy into TVET not only improves employability but also enables learners to become responsible digital citizens.